SPATIAL ANALISIS ABOUT THE ADJUSTMENT OF NJOP BASED ON ASSESSMENT RATIO (STUDY CASE : UJUNG BERUNG SUB DISTRICT, BANDUNG) - Rabbani, Atifah
Bandung is a city which has a high Local Own-source Revenue (PAD) with Land and Building Taxes (PBB P2) as one of the biggest contributor. Considering Bandung’s condition with a lot of development programs, PBB P2 can being optimized to increasing PAD. Tax Object Sales Value (NJOP) is the basis to determine PBB P2 and it has different value with land price. The difference between NJOP and land price is called Assessment Ratio (AR). Directorate General of Taxation (DJP) had already set 4 steps to do AR study that aims to analyze the performance of NJOP determination, they are central tendency test, progressivity/regressivity test and variability test. However, until now there are no research conducting the method to get AR study’s result that match the regulation. Hence, it is necessary to reveal it and this research is focused in developing AR test in the following step after getting the AR study’s result, that is revealing the method to fix the outlier value to equating the value in regulation. The result shows that Ujung Berung Subdistrict has spatial pattern and AR study’s result that is not equating the value of DJP’s regulation. After the simulation is being run, evidently the adjustment method with increasing NJOPs based on their land price group can improve the AR study’s result better. This NJOPs adjustment will rising PBB P2 to over 128.54% but at the same time will causing tax arrears in a large number of regions. To cope that risk, a policy to make a difference between tax arrears potentials and the non-tax arrears potentials is being offered. In this study case, the policy will increasing PBB P2 to over 107,87%.